A cross sectional comparative study of quality of life of treatments seekers at de-addiction centre in central India using WHO BREF scale - Kapse, Nitin S.; Thakre, Sushama S.; Thakre, Subhash B.; Kapse, Shushanki N. (International Journal Of Community Medicine And Public Health, 2017)
Background: Substance use disorders (SUDs) are a major global health problem affecting quality of life of human being. It has major impact on physical, psychological, social and environmental aspect of life. The aim is to assess Quality of Life (QoL) of persons seeking treatment at de-addiction centre by comparing it with those not seeking treatment, using WHOQOL BREF scale. Methods: A cross sectional comparative study is done on 250 persons admitted and seeking treatment at de-addiction centre during August 2014 to December 2015. A five-point scale rated WHOQOL-BREF questionnaire was used to assess quality of life. Results: Majority of study participants (85.60%) rated their quality of life as poor when compared to comparison group who rated their quality of life as good (52.80%). Majority of study participants (82.80%) were dissatisfied with their health. It was observed that the mean score of the physical, psychological, social and environmental domain in the study group was significantly lower in study group when compared to comparison group (p<0.001). Conclusions: Substance abuse had detrimental effect on the physical, social, psychological and environmental domain affecting their overall health and quality of life.